Dental schools in Brazil and their social, macro-regional and oral health policy repercussions: Dental schools in Brazil - Silveira , Roberta Machado; Menti , Luiza Deitos; Bernardo , Gustavo Almansa; Bidinotto, Augusto Bacelo; Hilgert , Juliana Balbinot; Neves, Matheus (Brazilian Dental Science, 2023)
Dentistry is a profession that has shown considerable growth in the last few years, as far as qualitative aspects and scientific production are concerned, and also in the number of undergraduate courses. Objective: to describe the profile of dentistry courses through official data and unofficial data, such as the existence of student support programs, gender disparities and availability of study places. Material and Methods: to this end, a survey of the 565 Dentistry courses registered by the Ministry of Education was carried out by three trained researchers and then of their respective websites and public domain information, followed by data analysis (R 4.1.2 R Core Team software, Vienna) and georeferencing (Qgis and ArcGis software). Results: as for the profile of the institutions that offer the course, 89.4% are private and as for the unofficial data, 63% of the sites do not have information regarding the teaching staff, 44.2% of the courses present a woman as coordinator and more than half report having at least one type of student support activity. It was possible to observe that the greatest availability of Dentistry vacancies is offered by private institutions and in courses coordinated by men. Conclusion: considering the information available on the college websites, it is important to keep them up to date and complete, so that students have access to the support activities that are relevant to their education. KEYWORDS Access to public information; Dental students; Faculties of dentistry; Gender equity; Public health.